Family Ownership, Cost of Debt, and The Moderation of Corporate Opacity - Purwoaji, Azam; Dianawati, Wiwiek (Akuntansi: Jurnal Akuntansi Integratif, 2025)
This study examines the moderating role of corporate opacity in the relationship between family ownership and the cost of debt in Indonesian manufacturing firms. Using a sample of 117 firms listed on the Indonesia Stock Exchange (IDX) from 2018–2020, the study employs multiple linear and moderated regression analysis. Results indicate that family ownership reduces the cost of debt, and this effect is significantly moderated by corporate opacity. The findings contribute to understanding the impact of transparency on debt financing in family owned firms, offering insights for lenders, regulators, and family businesses in managing financial strategies.